Health Literacy and Migrant Communities in Primary Health Care - Medina, Patrícia; Maia, Ana Catarina; Costa, Andreia (Frontiers in Public Health, 2022)
Introduction The promotion of health literacy of the population in a situation of migration, in the community, is a fundamental field of intervention in health promotion, for the reduction of inequalities in access to health care services. It is increasingly necessary to make health care services more equitable for migrant populations. The aim of the study was to characterize the level of health literacy of the population in a migrant situation, attending a primary health care unit in the Lisbon region, to identify priority areas for community intervention that will become the focus of intervention and contribute to the increase in the health literacy levels in this population. Methods A cross-sectional study was carried out by applying the Health Literacy Survey (ILS-PT) to a sample of the population in a situation of migration, found by 27 participants. Results The general health literacy index of the sample is inadequate (21.23 points). An analysis of the sub-indexes revealed that 75% of the participants had difficulties related to information about health care and 80% had difficulties in the field of health promotion. Conclusions Problematic and inadequate levels of health literacy was significantly frequent among migrant population. So that enhancing health literacy among migrant is essential to reduce health inequalities to achieve better health outcomes and contribute to defense of human rights of this vulnerable population.